Factors of Failure of the 2022 Rice Harvest for Local Rice Varieties of Banjar Rice - Muhammad Ilmiyanor; Ersis Warmansyah Abbas; Mahmudah Hasanah; Raihanah Sari; Muhammad Rezky Noor Handy (Journal of Social Development, 2023)
In 2022 farmers experienced rice crop failures caused by certain things that resulted in a decrease in Banjar's local rice supply. The purpose of this study was to determine the factors of rice crop failure experienced by rice farmers which resulted in a decrease in local rice supplies. This research study uses a qualitative method descriptive approach located in Anjir Serapat Muara I Village with data collection techniques through observation, interviews and documentation. The data collection was analyzed using data reduction techniques, data presentation, then Verification. Selanjutnya in testing the validity of data using triangulation and extended observation. The results of the research obtained by researchers that the factors of rice crop failure are caused by OPT, namely Tungro disease which breeds widely due to the rainy season and there is no dry season, This is supported by the condition of the La Nina phenomenon that is occurring in 2022 which has an impact on climate change which has an influence on the increase or spread of Tungro pest attacks. This rice harvest failure was not only experienced by Anjir serapat muara I farmers, but also felt by farmers in other sub-districts around Barito Kuala. This rice harvest failure made the acquisition of rice a little so that farmers suffered losses and local rice supplies became reduced, and caused local rice prices to be expensive.